IMPACT OF GOVERNMENT EXPENDITURE ONAGRICULTURAL OUTPUT AND POVERTY - Azhar Bafadal, Netti Tinaprilla, Muhammad Arsyad, Ayub M. Padangaran, La Ode Jabuddin, Asrul Sani, Siti Aida Adha Taridala (International Journal of Advanced Science and Technology, 2020)
Output in the agricultural sector is one of the measures of agricultural development success. However, financial intervention from both local and central government still become a crucial issue. The research objectives; (i) to analyze factors affecting government expenditure, agricultural output, and poverty, (ii) to analyze the impact of government expenditure on performance of agricultural output and poverty The research used pooled data. An econometric model in the form of a system of simultaneous equations was developed. The results show that; (1) the government expenditure was influenced by original regional revenue, balance funds, other legal revenues, direct-indirect expenditure and lag fiscal policy, (2) agricultural output performance and poverty were affected by labor, employment, direct expenditure, investment, land area per capita, total gross regional domestic product (GRDP), interest rates, population and lag of agricultural performance, (3) increasing government expenditure, on the direct expenditure point of view, has an impact on the increasing agricultural GRDP, declining labor, decreasing investment and declining poverty.  This implies that to increase output in agricultural sector and reduce poverty, it is necessary to increase fiscal capacity in addition to increase direct expenditure.